IMPROVING THE METHODOLOGY FOR RAISING THE OVERALL ENDURANCE OF GIRLS OF THE UPPER CLASS IN ATHLETICS CLUBS AT SCHOOL - Qazokov Sodiq Ramazonovich (TADQIQOTLAR, 2025)
Abstract: Athletics is very important for developing endurance and fitness among sports. Increasing the overall endurance of high school girls will further increase their interest in physical health and sports. This article presents suggestions for improving the methodology of endurance training in athletics circles.